containing the Old and New Testaments (London, 1989)
Though they are regularly used in both Protestant and Roman Catholic congregations, the books of the Apocrypha are difficult to find in affordable English Bibles today—until now!
Keywords: Old and New Testaments,Tân ước và Cựu ước